Electric-field structuring of piezoelectric composite materials - Wilson, Stephen A. (Cranfield University, 1999)
Piezoelectric composite materials, consisting of a ferroelectric ceramic in an electrically-inactive polymer matrix, have been shown to greatly outperform single phase materials for certain applications. A new assembly technique, which electrically controls the spatial distribution of the ceramic within the polymer, promises to enhance the sensitivity of 0-3 type piezoelectric composites. The materials so-produced have a quasi 1-3 structure and it is intended that they will exhibit some of the advantages of 1- 3 piezoelectric composites, whilst retaining the simplicity of 0-3 manufacturing. The electric field structuring technique exploits the electrokinetic phenomenon of dielectrophoresis, which is responsible for the electrorheological effect. When a suspension of ceramic particles in an insulating fluid is exposed to a moderate AC electric field, the particles polarize and as a result they exhibit a mutually attractive force. Under suitable conditions the particles assemble into `pearl-chains', `fibrils' or columns, oriented parallel to the applied field. If the fluid is a resin pre-polymer, this can then be cured and the newly formed structures frozen into place to form a composite material with anisotropic properties. The key process parameters are explored and the implications of employing this method to produce technologically useful materials are discussed. It is demonstrated, for the first time, that dielectrophoresis can be used to induce anisotropic dielectric and piezoelectric properties in 55%vol. fraction ceramic / polymer composites. A model composite system of pure lead titanate in an epoxy resin is considered in basic detail. A method of producing a lead zirconate titanate (PZT) powder with a narrow particle size distribution, by flux growth, has been shown to be effective. New concepts in multiphase composites are introduced, whereby chains are formed within the confines of a second immiscible fluid or where particles of two different materials are mixed in a suspension, each material having its own `polarization signature'.